Hypoxia-induced PYCR1 regulates glycolysis and histone lactylation to promote bladder cancer progression and metastasis via SLC6A14/Glutamine metabolism - Zhuo Li; Qinghua Jiang; Quan Yang; Yujie Zhou; Jiansong Wang (Cancer Biology & Therapy)
Hypoxia-induced Pyrroline-5-Carboxylate Reductase 1 (PYCR1) is implicated in bladder cancer (BC), but its specific role remains elusive. This study investigated how PYCR1 promotes BC progression through glycolysis, histone H3 Lysine 18 Lactylation (H3K18la), and Solute Carrier Family 6 Member 14 (SLC6A14)-driven glutamine catabolism. Here, BC cell lines were cultured under hypoxia to evaluate changes in PYCR1 expression, glycolysis, and lactate production. The xenograft and metastasis models in nude mice were used to validate the role of the PYCR1/H3K18la/SLC6A14 axis in BC progression. GEPIA Bioinformatics database data showed that PYCR1 was upregulated in BC and was associated with poor prognosis. The PYCR1 positive expression rate in BC tissues was increased. Hypoxia induced PYCR1 expression in BC cells, enhancing glycolysis and lactate production, which increased H3K18la levels. Upregulated SLC6A14 expression promoted glutamine catabolism and enhanced BC cell proliferation, migration, and invasion. PYCR1 knockdown inhibited H3K18la levels, SLC6A14 expression, and BC cell aggressiveness; SLC6A14 overexpression reversed these effects. In vivo experiments confirmed that the PYCR1/H3K18la/SLC6A14 axis is critical for hypoxia-driven BC growth and metastasis. In summary, Hypoxia-induced PYCR1 enhances glycolysis, leading to increased lactate production and elevated H3K18la levels, which upregulates SLC6A14 transcription and glutamine catabolism, thereby promoting BC growth and metastasis.